2021
DOI: 10.3390/pr9101747
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Porous Media Aperture Arrangement on CH4/Air Combustion Characteristics in Micro Combustor

Abstract: Micro-electro-mechanical systems (MEMS) occupy an important position in the national economy and military fields, and have attracted great attention from a large number of scholars. As an important part of the micro-electromechanical system, the micro-combustor has serious heat loss due to its small size, unstable combustion and low combustion efficiency. Aiming at enhancing the heat transfer of the micro-combustor, improving the combustion stability and high-efficiency combustion, this paper embedded porous m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…Combustion in porous media has been widely investigated and proven to be well-suited for lean combustion on a wide range of different fuels. In [6][7], the effect of a porous media arrangement was studied on a CH 4 /air combuster, and the experimental and simulation results indicated that the inner and outer layers had a positive impact on the combustion process. Many studies focused on the usage of liquid fuels, such as kerosene and ethanol [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Combustion in porous media has been widely investigated and proven to be well-suited for lean combustion on a wide range of different fuels. In [6][7], the effect of a porous media arrangement was studied on a CH 4 /air combuster, and the experimental and simulation results indicated that the inner and outer layers had a positive impact on the combustion process. Many studies focused on the usage of liquid fuels, such as kerosene and ethanol [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%